Multi Representation Ability of Students in Solving Physics Problems on Straight Motion - Paulina Nelce Mole; Rambu Ririnsia Harra Hau; Agustina Elizabeth (Variabel, 2022)
This study aims to describe the students' multi representation abilities in solving descriptive questions on straight motion material. This was qualitative research with an analytic descriptive approach. The subjects of this study were three physics teachers and twenty-five students of class X MIA SMA Negeri 1 Maumere. The data used in this study were evaluation questions, physical evaluation scores, student worksheets on evaluation questions and interview results. The data collection techniques used in this study were as follows: Documentation and in-depth interviews. For qualitative research data to be accounted for as scientific research, In this study, using triangulation techniques, checking data to the same source with different techniques, namely the results of observations, students' answers, and in-depth interviews. Data analysis techniques used in this study were grounded theory. The steps of grounded theory were: creating categories for the information obtained (open coding), selecting one of the categories and placing it in a theoretical model (axial coding), and then compiling a story of the relationship between these categories (selective coding). The results showed that students tend to use the same representation, such as verbal 12.5%, mathematical 87.5%, while graphics and pictures were 0%. For each category, students: (a) in the low category received a mathematical representation score of 73.81% and verbal representation was 83.3%, (b) in the moderate category received a verbal representation score of 85% and mathematically 83.06% (c) in the high category obtained a verbal representation score of 83.3% and mathematics 90.47%.